Advanced path simulation of a 5R robotic arm for CT guided medical procedures. (2018) - Shubham Kamlesh, Shah; Mishra, Ruby
Abstract: Robotics has been helping mankind since it was first developed and now it is used to save lives in medical field. But robotics is still in development phase in medical department and needs much research. Biopsy of a tumor and cancer tissue using CT scans is a sector where accuracy, space efficiency and cost efficiency is paramount. This research paper aims to design a robotic arm in such a way that only Cartesian coordinates obtained from a CT scan image are required to generate path of the end needle for a desired point with accuracy and space efficiency. Simulation and analyzation of the error in reaching the affected tissue is also done for this 5R and 3-DOF articulated robotic arm. This robotic arm will be cost effective as compared to other medical robotic arm currently in commercial supply. This robotic arm is modeled in CREO software. Transformation matrix were generated to find the equation for Cartesian coordinates that are to be input by user and Forward and Inverse kinematics were used to calculate the workspace in 3-D for the robotic arm in MATLAB. Path generation and Simulation is done in MATLAB to understand the level of error in reaching the affected tissue coordinate which was found to be very marginal and acceptable for medical applications. The material that can be used in manufacturing of this robotic arm is extruded Ketron PEEK GF30 (30% glass fiber reinforced). This grade is ideal for structural applications that require improved strength, stiffness and stability.